The Responsibility Of Business Actors In The Distribution of Blue-Labeled Skincare Products Through E-Commerce Based on Law Number 8 of 1999 - Ardhelia Putri Salsabila; Christine S.T. Kansil (Jurnal Ius Constituendum, 2025)
This study analyzes the legal responsibility of business actors in distributing blue-labeled skincare products through e-commerce platforms, particularly in relation to violations of Law Number 8 of 1999 on Consumer Protection, BPOM regulations, and the Electronic Information and Transactions Law. The urgency of this research arises from the widespread circulation of unauthorized dermatological products sold without BPOM approval, posing serious health risks to consumers in the digital marketplace. Employing a normative juridical method with a statutory and literature approach, this study examines the fragmentation of regulatory frameworks, liability avoidance strategies, and the ineffectiveness of current enforcement mechanisms. The findings reveal that business actors exploit regulatory gaps to avoid accountability and that existing laws are reactive and insufficient for digital contexts. This research contributes novelty by integrating pharmaceutical and e-commerce law in analyzing liability and proposes regulatory reforms that include platform liability mandates, automated monitoring systems, and public awareness campaigns. The study concludes that stricter law enforcement, increased regulatory oversight, and comprehensive stakeholder education are essential to protect consumers and ensure legitimate commerce in Indonesia's digital era.